Etika Penggunaan Media Sosial untuk Penginjilan: Antara Efektivitas dan Tantangan Moral - Fanli Feydi Pongoh; Gloria Gabriel Lumingas; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
The development of digital technology has significantly transformed communication patterns and church ministry. This study aims to analyze the effectiveness of social media as an instrument of evangelism and to examine the ethical challenges emerging in the digital context. The research employs a descriptive qualitative method through literature analysis, national statistical data, and theological reflection grounded in Christian ethics. The findings reveal that social media is effective in expanding the reach of evangelism, yet simultaneously generates moral issues such as disinformation, hate speech, privacy violations, and digital fatigue. The novelty of this research lies in developing a four–pillar ethical framework for digital evangelism, content transparency, digital literacy, pastoral digital care, and community accountability contextualized for the Indonesian church in the 21st century. This framework not only addresses the practical needs of ministry in digital spaces but also contributes theoretically to digital theology by emphasizing the integration of media effectiveness and moral responsibility in contemporary evangelism.